2015
DOI: 10.1155/2015/289647
|View full text |Cite
|
Sign up to set email alerts
|

Change of Scaling‐Induced Proinflammatory Cytokine on the Clinical Efficacy of Periodontitis Treatment

Abstract: Proinflammatory cytokines are key inflammatory mediators in periodontitis. This study aimed to investigate the relationship between proinflammatory cytokines in saliva and periodontal status. To investigate the usefulness of cytokines in the therapeutic approach for periodontal disease, the relationship between stimulated cytokine changes and the periodontitis treatment outcome was investigated in this study. Saliva was obtained from 22 patients diagnosed by dentists as having chronic periodontitis. The proinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…In addition to the mentioned studies, Shy [ 30 ] study reported increase in TNF-α level after non-surgical treatment and improvement in clinical indices. Despite common belief that periodontal pathogens cause progressive destruction of periodontal tissue via severe immune response induction, some in vitro studies showed that periodontal pathogens, compared to non-pathogenic factors, cause lower level of inflammatory cytokines induction [ 45 - 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the mentioned studies, Shy [ 30 ] study reported increase in TNF-α level after non-surgical treatment and improvement in clinical indices. Despite common belief that periodontal pathogens cause progressive destruction of periodontal tissue via severe immune response induction, some in vitro studies showed that periodontal pathogens, compared to non-pathogenic factors, cause lower level of inflammatory cytokines induction [ 45 - 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shy study reported that salivary IL-1α level increased in patients who responded to treatment [ 30 ]. In Front study, IL-1α level showed a decrease by 51% after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been suggested that IL1β can discriminate between inactive and active periodontal lesions, there are very few diagnostic accuracy studies that have investigated it in saliva as a way to evaluate the response to periodontal treatment (Lee, Chen, Tu, Wu, & Chang, 2018; Shyu et al, 2015). The methodological approach in the present paper is different because we evaluate for the first time the capacity of IL1β in saliva to distinguish untreated from treated periodontitis demonstrating clinical improvement and differentiating between non‐smokers and smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators are activated when bacteria accumulates in the gingival region. 2,4,5 Interleukin-1 is a term for some cytokine polypeptides, such as IL-1α, IL-1ß, and IL-1ra, which play an essential role in the regulation of the immune system and the inflammatory response. Macrophages or lymphocytes activate interleukin-1; otherwise, it can be produced by other cells, including mast cells, fibroblasts, keratinocytes, and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%